2008
DOI: 10.1111/j.1468-2494.2008.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Poly(D,L‐lactide) nanoencapsulation to reduce photoinactivation of a sunscreen agent

Abstract: The use of sunscreens is the 'gold standard' for protecting the skin from ultraviolet light. Octyl methoxycinnamate (OMC) is one of the most widely used UVB filter but it can act as a sensitizer or photoallergen. When exposed to sunlight, OMC can change from the primary trans-form to cis-form and the isomerization, not reversible, conducts to a reduction of the UVB filtering efficiency because the trans-form has a higher extinction coefficient. Photostability is the most important characteristic of effective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The results supported the hypothesis that OMC is protected in nanoparticles and that PLA nanoencapsulation could be used to prevent photoisomerization. An in vitro filter efficacy experiment demonstrated that no SPF could be associated to the nanoparticles whereas the obtained protective effect by OMC was not altered by encapsulation of the sunscreen in nanoparticles [22].…”
Section: Increasing the Photostability Of Existent Sunscreensmentioning
confidence: 99%
“…The results supported the hypothesis that OMC is protected in nanoparticles and that PLA nanoencapsulation could be used to prevent photoisomerization. An in vitro filter efficacy experiment demonstrated that no SPF could be associated to the nanoparticles whereas the obtained protective effect by OMC was not altered by encapsulation of the sunscreen in nanoparticles [22].…”
Section: Increasing the Photostability Of Existent Sunscreensmentioning
confidence: 99%
“…Similar to SLNs, poly(d,l-lactide) (PLA), is an established polymer in the drug delivery industry. Nanoencapsulation of octinoxate using PLA results in increased photostability [23]. Similarly, a study by the same research group show that encapsulating octinoxate with poly-d,l-lactide-co-glycolide (PLGA) also has greater photostability than octinoxate alone [24].…”
Section: Polymeric Nanoencapsulationmentioning
confidence: 93%
“…Embedding in polymethylmetacrylate reduced the amount of sunscreen released from the cream and increased minimal erythemal dose and SPF [73]. In another paper, poly(d,l-lactide-co-glycolide) and poly(d,llactide) polymers protected EMC from photodegradation [74,75] whereas ethylcellulose failed [74].…”
Section: Polymeric Microparticlesmentioning
confidence: 93%